Leadership needs time : the role of temporal cognitions for leadership processes and outcomes - Briker, Roman; Justus Liebig University Giessen (My University, 2019)
This dissertation aimed to develop a new, more context-specific view toward the implications of leaders and followers temporal cognitions for leadership processes and outcomes. Across three independent research projects, using state-of-the-art methodological and analytical approaches and drawing from different samples and contexts, I investigated the roles of leaders and their followers time urgency, temporal focus, and time pressure for relevant behaviors and consequences related to both formal and informal leadership. In particular, Chapter 2 showed that highly time-urgent supervisors were more likely to engage in autocratic leadership behavior when they perceived their status among their subordinates to be high, but not when such perceptions were low. In turn, highly time-urgent supervisors autocratic acts increased individual subordinates perceptions of work stress and time pressure. Chapter 3 demonstrated that supervisors engaged more in both task-oriented and relationship-oriented leadership the more their own and their team s past temporal focus were incongruent. Moreover, when supervisor and team past temporal focus were aligned, supervisors demonstrated less task-oriented and relationship-oriented leadership and more laissez-faire leadership in situations of congruence at high (as opposed to low) levels of past temporal focus. Finally, Chapter 4 s findings indicate that actors time pressure is positively associated with their time-oriented behavior toward the interaction partner and that the linkage between actors time pressure and relationship-oriented behavior is moderated by partner time pressure. In particular, the results suggest that the latter linkage was positive when the partner s time pressure was relatively high but negative when the partner s time pressure was relatively low. All in all, this dissertation enriches leadership theory and research with a subjective temporal perspective, demonstrating that both leaders and followers orientations toward and perceptions of time critically shape processes of leadership.
Führung benötigt Zeit : die Rolle von zeitlichen Kognitionen für Führungsprozesse und -auswirkungen
Keywords: Zeit; Führung; time; leadership; ddc:650